POLISH LANGUAGE IN KALININGRAD (RUSSIA) AT THE BEGINNING OF THE 21ST CENTURY - FOREIGN, SECOND OR NATIVE LANGUAGE? - Grochowina, Małgorzata; Zubritskaya, Ekaterina (Revista X, 2020)
The main purpose of the article is to present the situation of the Polish language in Kaliningrad, the main administrative centre of the Kaliningrad region, the westernmost territory of the Russian Federation. Polish has been present in this area for centuries as foreign, second or native language depending on the nationality and origin of its users. Currently, people who live in Kaliningrad, have an opportunity to learn Polish at three institutions of various types. They are Polish diaspora organizations, private language schools and language courses, and state educational institutions, with Immanuel Kant Baltic Federal University between them. This article presents the results of our research which aims to identify the status of the Polish language among the students who attend Polish classes. The survey took the form of questionnaires, was anonymous and voluntary, and involved people from each of the organizations mentioned above.